Surface modification of PEN treated with ozone and UV photooxidation. Issue 1 (March 2016) - Al Abdulal, Entesar; Bailey, Alla; Mehan, Michael; Gupta, Surendra Kumar; Li, Xinyun; Toro, Marc; Takacs, Gerald Alan
Abstract : Poly(ethylene 2, 6-naphthalate) (PEN) was treated with ozone in the absence of radiation and the results were compared with ultraviolet (UV) photooxidation using 253·7 and 184·9 nm radiations. The surface modification of the top 2–5 nm was analyzed by X-ray photoelectron spectroscopy (XPS) for chemical changes. Higher saturation levels of oxidation were achieved using UV photooxidation than ozonation. Both treatment methods increased the amounts of C–O–C, C=O and O–C=O bondings while UV photooxidation also increased the concentration of the anhydride/carbonate moieties on the surface. Atomic force microscopy detected smoother surfaces with increasing treatment time for both the treatments. The changes in functional groups and surface roughness with both treatments contributed to an increase in hydrophilicity as determined by advancing water contact angle measurements. A greater increase in hydrophilicity was observed for the UV photooxidized PEN samples. Initial results showed a slight increase in hydrophilicity when acrylic acid was grafted onto ozone-treated PEN surfaces, although, the ester group in the PEN structure made it difficult to detect poly(acrylic acid) by XPS.